2022
DOI: 10.1002/cyto.b.22061
|View full text |Cite
|
Sign up to set email alerts
|

A series of case studies illustrating the role of flow cytometry in the diagnostic work‐up of myelodysplastic syndromes

Abstract: Current guidelines recommend flow cytometric analysis as part of the diagnostic assessment of patients with cytopenia suspected for myelodysplastic syndrome.Herein we describe the complete work-up of six cases using multimodal integrated diagnostics. Flow cytometry assessments are illustrated by plots from conventional and more recent analysis tools. The cases demonstrate the added value of flow cytometry in case of hypocellular, poor quality, or ambiguous bone marrow cytomorphology. Moreover, they demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In addition, this method confirmed the discriminative value of CD36 and CD71 MFI CVs for the erythroid lineage. It has also identified an increased SSC of more mature erythroid cells as a highly informative feature of MDS‐associated dysplasia (Duetz et al, 2021 ; Westers et al, 2023 ). This finding was independently confirmed by others using traditional analysis (Johansson et al, 2021 ).…”
Section: Computational Analysis/future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this method confirmed the discriminative value of CD36 and CD71 MFI CVs for the erythroid lineage. It has also identified an increased SSC of more mature erythroid cells as a highly informative feature of MDS‐associated dysplasia (Duetz et al, 2021 ; Westers et al, 2023 ). This finding was independently confirmed by others using traditional analysis (Johansson et al, 2021 ).…”
Section: Computational Analysis/future Directionsmentioning
confidence: 99%
“…However, results of a survey concerning current MFC practice in 229 laboratories around the world showed that although many laboratories used large numbers of markers in MFC workup of MDS (median: 20 ± 4.5), the compliance with i MDSflow recommendations was low, and proposed scoring systems were not widely applied (Grille Montauban et al, 2019 ; Jensen et al, 2019 ). With the hope of increasing the harmonization of MFC MDS diagnostics, the current paper presents a summary of the progress in this field and an update on consensus i MDSFlow guidelines for the assessment of significant anomalies in various bone marrow (BM) cell compartments for MFC features of dysplasia as a part of a special Issue of Clinical Cytometry B, focused on MFC applications in MDS and MDS/MPN (Kern et al, 2022 ; van de Loosdrecht et al, 2023 ; van der Velden et al, 2023 ; Wagner‐Ballon et al, 2023 ; Westers et al, 2021 ; Westers et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the working group has agreed that FCM is a rapid tool that complements and adds to routine diagnostic investigations in patients with undiagnosed cytopenias and suspected MDS and/or CMML. In this special issue of Cytometry Part B Clinical Cytometry, a series of case studies is presented to illustrate the role of FCM in the diagnostic workup of MDS (Westers et al, 2021). The value of FCM in assessing the prognosis of MDS beyond that of molecular variant analysis, is not yet established but FCM may be useful in predicting and monitoring disease during treatment with standard therapeutic regimens such as erythropoiesis stimulating and hypomethylating agents.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, concurrent autoimmune diseases and/or systemic inflammatory syndromes have been reported in up to 20% of CMML patients (Zahid et al, 2017). The usefulness of the 6‐sulfo LacNac (slan) as a specific marker of ncMo population (Hofer et al, 2019) has been recently demonstrated for the identification of this particular type of CMML associated with inflammatory state (Tarfi et al, 2019; see in illustrative case in Westers et al, 2022).…”
Section: Discussionmentioning
confidence: 99%